2018
DOI: 10.1002/hed.25462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor budding in head and neck squamous cell carcinoma: A meta‐analysis

Abstract: Tumor budding (TB) has been suggested as an adverse prognostic factor in head and neck squamous cell carcinoma (HNSCC). This meta‐analysis evaluated the prognostic role of TB in HNSCC. We systematically reviewed the literatures of electronic databases and performed a meta‐analysis to address the impact of TB on prognosis in HNSCC. Published data were extracted and organized. Then, pooled odds ratios for lymph node metastasis (LNM) and hazard ratios for survival were calculated by using the Mantel‐Haenszel fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 56 publications
(128 reference statements)
2
52
0
Order By: Relevance
“…Previously, we and other researchers found that tumor budding was correlated with lymph node metastasis and poor survival according to assessment method reported by Ueno . Importantly, meta‐analyses also revealed that high tumor budding scores indicated a poor prognosis in head and neck squamous cell carcinoma and oral squamous cell carcinoma . In this study, similar results were observed in an OTSCC patient cohort based on the ITBCC scoring system.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previously, we and other researchers found that tumor budding was correlated with lymph node metastasis and poor survival according to assessment method reported by Ueno . Importantly, meta‐analyses also revealed that high tumor budding scores indicated a poor prognosis in head and neck squamous cell carcinoma and oral squamous cell carcinoma . In this study, similar results were observed in an OTSCC patient cohort based on the ITBCC scoring system.…”
Section: Discussionsupporting
confidence: 85%
“…Accumulating evidences have implicated tumor budding as a strong and valuable independent prognostic factor in many solid cancers . Moreover, evaluation of tumor budding in biopsy specimens also might provide useful prognostic information, indicating a promising clinical application for patient diagnosis and treatment .…”
Section: Discussionmentioning
confidence: 99%
“…the correlation of NLM with TBG, but they were limited to high TBG cases (13,14). In our previous study (15), we found that TBG is the most important prognostic factor for the early T-stage tongue SCC.…”
Section: Podoplanin Is An Efficient Predictor Of Neck Lymph Node Metamentioning
confidence: 81%
“…Scoring of tumor budding is cost-effective and many studies on tumor budding have followed the guidelines for reporting recommendations for tumor marker prognostic studies (REMARK). 33 In laryngeal cancer, Sarioglu et al 8 were the first to evaluate tumor budding in HNSCC and they reported the prognostic power of tumor budding to predict distant metastasis in laryngeal carcinoma. Of note, our recent systematic search found 16 studies on tumor budding in OSCC and the meta-analysis confirmed the significance of tumor budding in prognostication of lymph node metastasis and survival.…”
Section: Tumor Budding As a Simple Promising Prognostic Marker In Hmentioning
confidence: 99%
“…10 Subsequently, after that meta-analysis many studies have been published indicating that tumor budding is a promising prognostic marker in OSCC, 21,[29][30][31][32] including the recent meta-analysis with tumors from various subsites of the head and neck. 33 In laryngeal cancer, Sarioglu et al 8 were the first to evaluate tumor budding in HNSCC and they reported the prognostic power of tumor budding to predict distant metastasis in laryngeal carcinoma. More recent studies have confirmed the prognostic value of tumor budding in laryngeal cancer.…”
Section: Tumor Budding As a Simple Promising Prognostic Marker In Hmentioning
confidence: 99%